2015
DOI: 10.4238/2015.april.13.3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between sheep YAP1 temporal and spatial expression trends and MSTN and MyoG gene expression

Abstract: ABSTRACT. The aim of the current study was to investigate the effects of Yes-associated protein 1 (YAP1) gene expression after birth on the development of muscle and the relationship between YAP1 and myostatin (MSTN) and myogenin (MyoG). Reverse transcription polymerase chain reaction was used to analyze the trends in YAP1, MSTN, and MyoG temporal and spatial expression levels in various skeletal muscles (i.e., longissimus dorsi muscle, soleus muscle, gastrocnemius muscle, and extensor digitorum longus) and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…One potential explanation is that the functions of miR-29a differ between species. In addition, several studies have revealed similar expression profiles between MyoG (Lv et al, 2015), MyHC (Gao et al, 2016), and YAP1 (decreases with age), indicating that miR-29a may inhibit both YAP1 and genes related to differentiation in Hu sheep SMSCs. Another potential explanation is that, in addition to YAP1, there might be other genes targeted by miR-29a involved in the proliferation and differentiation of SMSCs.…”
Section: Discussionmentioning
confidence: 85%
“…One potential explanation is that the functions of miR-29a differ between species. In addition, several studies have revealed similar expression profiles between MyoG (Lv et al, 2015), MyHC (Gao et al, 2016), and YAP1 (decreases with age), indicating that miR-29a may inhibit both YAP1 and genes related to differentiation in Hu sheep SMSCs. Another potential explanation is that, in addition to YAP1, there might be other genes targeted by miR-29a involved in the proliferation and differentiation of SMSCs.…”
Section: Discussionmentioning
confidence: 85%
“…Zhang et al [38] studied the expression of the myogenin gene in chickens and showed that this gene expresses in the breast muscle, leg muscle, heart, liver, spleen, lung, kidney, glandular stomach, and ovarian tissues. Lv et al [39] and Forutan et al [40] demonstrated that the myogenin gene expresses in different skeletal muscles of sheep, such as the soleus, gastrocnemius, longissimus dorsi, and extensor digitorum longus muscles. Kuang et al [41] reported the expression of the myogenin gene in the skeletal muscles of rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…(Siqin et al, 2017) reported that the MYOG and MYF6 gene expression levels in the LD muscle were stable during postnatal development in the fat-tailed Wuzhumuqin sheep breed. A study investigating these effects on muscle development in short-tailed Hu sheep found that the expression level of the MYOG gene was low (down-regulated) in the LD muscle, whereas the expression level was high (upregulated) in the gastrocnemius and soleus muscles, reporting the dependence of the expression level of the MYOG gene on the muscle groups as one of the reasons for this difference (Lv et al, 2015). In support of this view, this study found that the MYOG gene and protein expression level was statistically signi cantly (P < 0,05) high (up-regulated) in the LD muscle in the thin-tailed Karayaka sheep breed, while the expression level of the same gene and protein was low in the GL muscle (P < 0,05).…”
Section: Discussionmentioning
confidence: 99%